Structured groups make more accurate veracity judgements than individuals. Issue 6 (8th November 2021) - Hamlin, Iain; Bolger, Fergus; Vasilichi, Alexandrina; Belton, Ian; Crawford, Megan M.; Sissons, Aileen; Taylor Browne Lūka, Courtney; Wright, George
Abstract: Groups often make better judgements than individuals, and recent research suggests that this phenomenon extends to the deception detection domain. The present research investigated whether the influence of groups enhances the accuracy of judgements, and whether group size influences deception detection accuracy. Two‐hundred fifty participants evaluated written statements with a pre‐established detection accuracy rate of 60% in terms of veracity before viewing either the judgements and rationales of several other group members or a short summary of the written statement and revising or restating their own judgements accordingly. Participants' second responses were significantly more accurate than their first, suggesting a small positive effect of structured groups on deception detection accuracy. Group size did not have a significant effect on detection accuracy. The present work extends our understanding of the utility of group deception detection, suggesting that asynchronous, structured groups outperform individuals at detecting deception.